Jovens em movimento: o processo de formação da Pastoral da Juventude do Brasil. - Sofiati, Flávio Munhoz (Universidade Federal de São Carlos, 2004)
The object of this research is the formation process of the PJB, be it, its pedagogic method and its political options. The analysis is developed from a historical background in order to identify the changes occurred in the PJB method along the 1980 and 1990 decades. We can conclude that, during the 1980s, the PJB emphasized the political dimension in its formation activities and participated in several social movements, which were being organized around the proposal of Brazilian redemocratization. However, along the 1990s a reformulation of the method occurs and it passes to direct its formation to the personal and theological dimensions, having its practice turned to the inside of the Catholic Church. Internal factors, such as the back of Pentecostal movement to the catholic religious scenery, which has represented some drawbacks to the PJB articulation with the parish youth groups, as well as external factors, such as the arrival of the postmodern culture to the Brazilian society, which has brought the predominance for individualist practices, be it, without collective/communitarian basis, both contributed to these changes.
Keywords: Sociologia da religião; Catolicismo; Juventude; Formação política; Teologia da libertação; CIENCIAS SOCIAIS APLICADAS